2003
DOI: 10.1007/s00018-003-3298-y
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human glutamate dehydrogenase by aluminum

Abstract: Aluminum inactivated glutamate dehydrogenase (GDH) by a pseudo-first-order reaction at micromolar concentrations. A double-reciprocal plot gave a straight line with a k(inact) of 2.7 min(-1) and indicated the presence of a binding step prior to inactivation. The inactivation was strictly pH dependent and a marked increase in sensitivity to aluminum was observed as the pH decreased. At a pH higher than 8.5, no inactivation was observed. The completely inactivated GDH contained 2 mol of aluminum per mole of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
2
16
0
1
Order By: Relevance
“…In our electrochemical studies, at the physiologically relevant pH values (pH 6.5 and 7.5), the activity of the GDH enzyme was strongly dependent on the concentration of the metal ion in the assayed mixture solutions. These experimental results are in good agreement with recently biological findings [2,5,6]. Therefore, it is concluded that the Al(III) bioavailability depends not only on the species and its structure, but also on its concentration and the pH value.…”
Section: Biological Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…In our electrochemical studies, at the physiologically relevant pH values (pH 6.5 and 7.5), the activity of the GDH enzyme was strongly dependent on the concentration of the metal ion in the assayed mixture solutions. These experimental results are in good agreement with recently biological findings [2,5,6]. Therefore, it is concluded that the Al(III) bioavailability depends not only on the species and its structure, but also on its concentration and the pH value.…”
Section: Biological Effectssupporting
confidence: 92%
“…In the presence of a ring, like that of a double bond, prevents rotation, cis and trans isomers are possible. From the above constitutional studies on the keto-enol tautomerization of the Al(III) complexes with a-KG, it is also shown that different configurations of the isomers have [3][4][5]. The most stable enol-form isomers were isomers 4 and 5 based on the energy calculations.…”
Section: Configurational Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Al inhibits a large number of ATPdependent reactions and thus hampers energy-dependent processes (Silva et al, 2005;Szyperska et al, 2006). Reports have suggested that Al exposure can lead to impairment in glucose utilization, followed by altered activities of glucose-metabolizing enzymes, such as hexokinase and glutamate dehydrogenase (Yang et al, 2003;Dua et al, 2010). Zatta et al (2000) have observed alterations in the enzyme activities of both glycolytic and Kreb's cycle pathways.…”
mentioning
confidence: 97%
“…We found that GDH activity was reduced in nodules at all the levels of Al stress. This unexpected decline in GDH may be because of its inactivation by Al, which induces a conformational change (induced by Al binding) similar to that observed in human GDH (Yang et al 2003) or a correlated inhibition resulting from a concomitant inhibition of nodule GS (Glevarec et al 2004). However, there was a significant increment in GDH activity in roots at the highest level of Al stress, although only one isoform could be detected.…”
Section: Discussionmentioning
confidence: 86%